(untitled) (Bangladesh Journal of Medical Science, 2025)
Background The incorrect use of medications and/or non-adherence to drug therapy, which has an impact on health, the environment, and healthcare systems, make home medicine storage a global public health concern. The drug take-back programs are also common in some county to resolve this issue. Knowledge is one of predisposition of practice to dispose drug waste. Aim of this revies was to performed knowledge of public, prevalence of drug dispose method, and characteristics of variables within some resources Material and methods This systematic review and meta-analysis were conducted with prisma (systematic review and meta-analyses) method. Eligibility cirteria was performed on 3 databases (pubmed, scopus, and sciencedirect). Result Total respondent on this review were 3.480 respondent in public or community. Respondent that obtained and had knowledge about how to dispose drug were 39,5%. The most frequent method for disposal is throwing to the houshold garbage (68,6%). Only 6,6% respondent who return the unused drug to the pharmacy. It can be concluded that the knowledge about method of dispose the unused drug were still poor. Common method to dispose the drug was throwing to the household garbage. Conclusion The knowledge about method of dispose the unused drug were still poor although education level is high. The need of people about proper guideance to dispose medicinal waste and information of take-back progam. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 51-57